A WeChat Mini Program-Based Intervention for Physical Activity, Fruit and Vegetable Consumption Among Chinese Cardiovascular Patients in Home-Based Rehabilitation: A Study Protocol - Duan, Yanping; Li, Xin; Guo, Lan; Liang, Wei; Shang, Borui; Lippke, Sonia (Frontiers in Public Health, 2022)
Background: Cardiac rehabilitation programs aim to avoid further progression and relapse of cardiovascular diseases (CVD). Patients with CVD undergoing rehabilitation often experience difficulties in integrating and transferring the learned health behaviors into their daily life after returning home. This includes regular physical activity (PA) and sufficient fruit and vegetable consumption (FVC). eHealth individualized interventions have shown to be effective in increasing PA and FVC at home settings. As WeChat is the most popular social media site in China, this should be used for the intervention. The aim of this study is to develop and examine a WeChat mini program-based intervention on PA and FVC promotion among Chinese CVD patients in home-based rehabilitation. Methods: The study will adopt a randomized controlled trial (RCT), comprising a WeChat mini program-based intervention group and a waiting-list control group. The intervention content will be designed based on the Health Action Process Approach (HAPA). 158 outpatients will be recruited from the cardiac rehabilitation center of a hospital in southern China and randomly assigned to one of the two groups. During the 10-week duration of the intervention, participants will be invited to access a WeChat mini program comprising two Modules. Module 1 provides weekly learning sessions addressing PA and FVC simultaneously for 10 weeks. Module 2 provides a platform, where participants can review their progress with Module 1 at any time and attend incentive activities aiming at promoting engagement and retention. The outcome variables include PA (mins/week), FVC (portion/day), healthy lifestyle (the synthesis of PA and FVC), social-cognitive predictors of behavior change (risk perception, outcome expectancies, self-efficacy, intention, planning, social support, and action control) as well as health outcomes (Body mass index, depression, and quality of life). Data collection will be implemented at pre-test, post-test and 3-month following post-test respectively. Discussion: The current study will be significant to understand how such a cost-effective social media mini program-based intervention enables participants to adopt and maintain a healthy lifestyle. If it is effective, it will enrich home-based cardiac rehabilitation approaches which can in turn save the lives of patients as well as much monetary, time and other investments.